(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In our work, our objective is to prove the existence and uniqueness of a weak solution to a class of nonlinear degenerate elliptic (p, q)-Laplacian problem with Dirichlet-type boundary condition by giving L^ ∞ data. The principal technique utilized here is the variational method alongside the theory of Orlicz spaces and Minty-Browder theorem.